The Promise of Liquid Biopsy to Predict Response to Immunotherapy in Metastatic Melanoma - Fattore, Luigi; Ruggiero, Ciro Francesco; Liguoro, Domenico; Castaldo, Vittorio; Catizone, Angiolina; Ciliberto, Gennaro; Mancini, Rita (Frontiers in Oncology, 2021)
Metastatic melanoma is the deadliest form of skin cancer whose incidence has been rising dramatically over the last few decades. Nowadays, the most successful approach in treating advanced melanoma is immunotherapy which encompasses the use of immune checkpoint blockers able to unleash the immune system’s activity against tumour cells. Immunotherapy has dramatically changed clinical practice by contributing to increasing long term overall survival. Despite these striking therapeutic effects, the clinical benefits are strongly mitigated by innate or acquired resistance. In this context, it is of utmost importance to develop methods capable of predicting patient response to immunotherapy. To this purpose, one major step forward may be provided by measuring non-invasive biomarkers in human fluids, namely Liquid Biopsies (LBs). Several LB approaches have been developed over the last few years thanks to technological breakthroughs that have allowed to evaluate circulating components also when they are present in low abundance. The elements of this so-called “circulome” mostly encompass: tumour DNA, tumour and immune cells, soluble factors and non coding RNAs. Here, we review the current knowledge of these molecules as predictors of response to immunotherapy in metastatic melanoma and predict that LB will soon enter into routine practice in order to guide clinical decisions for cancer immunotherapy.